ANALYSIS OF BUSINESS FEASIBILITY OF BANANA CHIPS - Ruswaji, Ruswaji; Cahyono, Puguh (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2020)
In this study, the method used is the Net Present Value (NPV) method, Internal Rate of Return (IRR), Payback Period (PP) and Break Event Point (BEP). The results of the study show that the net present value (NPV) is Rp. 31,024,617, - and is feasible because the NPV 0, the Internal Rate of Return (IRR) of 8.25% is feasible because it is greater than the deposit interest value applicable to for the bank at this time, the Payback Period (PP) of 2 months is feasible because it is still smaller than the investment period, and the Break Event Point (BEP) of Rp.44,828,693 is feasible because the business is not profitable and does not lose if it earns income. amounting to Rp. 44,828,693, - The banana chip entrepreneurs still maintain the drying of banana chips by using solar energy, because the considerations of raw material prices and production and marketing costs are very sensitive to affect sales and profits.